HUBUNGAN MEKANISME CIDERA DAN USIA DENGAN NILAI GCS PADA PASIEN CIDERA KEPALA DIRUANG IGD RUMAH SAKIT UMUM DR. ACHMAD MOCTAR BUKITTINGGI - Ida Suryati; Wita Esma (JURNAL KESEHATAN PERINTIS, 2015)
Injury large role in determining the determining the severity of the patofisiological consequences of a head trauma. Accerelation injury occurs when a moving object hitting stationary head, as a result of blunt trauma or because the throw blunt. Le deceleration injury when the head which is relatively immobile such as automobile bodies or soil.The purpose of this study was to look at the factors that affect the value of GCS in patients with head injury in emergency rooms RSAM Bukittinggi year 2015. This study used a descriptive design Koleratif, namely a review of the situation between the two variables or groups of objects, independent dependent variable. With 41 respondents were taken by purposive sampling technique. Data collection is done by using a sheet of interviews conducted in August 2015. Based on the research note that the apparent mechanism of head injury patients in accelerated category (29.3%), deceleration (39.0%) and deformation (31.7%).By age of head injury patients seen in the adult category (39.0%), older adults (46.3%) and the elderly (14.6%). From the statistical test was obtained p = 0.003 (p = <0.05) means that there is a connection mechanism of injury with GCS score of head injury patients. From the statistical test obtained with the age of the patient GCS score of head injury by chi-square test obtained by value p = 0.004 (p = <0.05), meaning there is a relationship of age with a GCS score of head injury patients. From the results of this study concluded that there is a relationship between the mechanism of injury and age with a GCS score of head injury patients. Hopefully this research can be used as the field of research and service diruang ER nurse RSAM Bukittinggi to pay more attention to the value of GCS patients of head injury caused by acceleration, deceleration and deformation.